2010
DOI: 10.2172/974465
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seismic Load Demand for a Wind Turbine in the Time Domain: Preprint

Abstract: UL 18. NUMBER OF PAGES 19a. NAME OF RESPONSIBLE PERSON a. REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 13 publications
10
48
0
Order By: Relevance
“…In particular, considering that the results of load case LC3 do not seem affected by the rotor position, a 0 • parked state is assumed. For a given load case, two simulations are carried out for each earthquake, in agreement with the studies by Prowell et al [9,10] on land-based HAWTs. The two simulations differ as the two horizontal components of the earthquake are rotated 90 • , in order to reduce bias from the orientation of the earthquake components relative to the wind direction [9,10].…”
Section: Response To An Earthquake Setmentioning
confidence: 93%
See 3 more Smart Citations
“…In particular, considering that the results of load case LC3 do not seem affected by the rotor position, a 0 • parked state is assumed. For a given load case, two simulations are carried out for each earthquake, in agreement with the studies by Prowell et al [9,10] on land-based HAWTs. The two simulations differ as the two horizontal components of the earthquake are rotated 90 • , in order to reduce bias from the orientation of the earthquake components relative to the wind direction [9,10].…”
Section: Response To An Earthquake Setmentioning
confidence: 93%
“…Wind and wave environmental states, water depth and soil profile are set in agreement with similar theoretical studies on offshore HAWTs [18,19]. Consistently with the approach followed for land-based HAWTs [9][10][11], the seismic response is investigated for a set of real earthquake records taken from existing databases [20,21], with different frequency content and intensity. Fully coupled nonlinear time-domain simulations are carried out on full system models including nonlinear soil stiffness, using the BLADED software package [22], certified by Germanischer Lloyd for design of wind turbines.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As a lower-bound, a nacelle ac celeration of Im/s^ was investigated. Prowell et al (2010) suggested this value as the point a t which an emergency shut-down could be induced in the wind turbine system in order to avoid severe damage to sensitive equipment. It was found th a t each record in the suite of ground motions induced this minimum acceleration in all 6 towers.…”
Section: Apacity E Stim Ationmentioning
confidence: 99%